Changes in the functional properties of casein conjugates prepared by Maillard reaction with pectin or arabinogalactan. (March 2023) - Yang, Siqi; Zhang, Guofang; Chu, Hong; Du, Peng; Li, Aili; Liu, Libo; Li, Chun
Graphical abstract: Highlights: Casein formed conjugates with pectin or arabinogalactan through Maillard reaction. Conjugates had lower α-helix level and higher random coil level of casein. Conjugates had lower surface hydrophobicity and higher absolute ζ-potential values. Glycosylation treatment significantly improved the functional properties of casein. Abstract: The aim of this study was to prepare conjugates of casein (CA) with pectin (CP) or arabinogalactan (AG) by the Maillard reaction (wet-heating) and to investigate the effects of CP or AG on the structural and functional properties of casein. The results indicated that the highest grafting degree of CA with CP or AG was observed at 90 °C for 1.5 h or 1 h, respectively. Secondary structure showed that grafting with CP or AG reduced the α-helix level and increased the random coil level of CA. Glycosylation treatment of CA-CP and CA-AG exhibited lower surface hydrophobicity and higher absolute ζ-potential values, further significantly improving the functional properties of CA (e.g., solubility, foaming property, emulsifying property, thermal stability, and antioxidant activity). Accordingly, our results indicated that it is feasible for CP or AG to improve the functional properties of CA by the Maillard reaction.